Engineering the Bioelectronic Interface
Written by leaders in the field, this is the only book to focus on the generation of biosensing interfaces with analyses and control at the molecular level. Some of these are enzyme based, others associated with the generation of surfaces for protein-protein recognition. Summaries of state-of-the-art investigations into the interfacing of structurally complex molecular species with electrode surfaces are included along with their design, analysis and potential application. Studies into the \wiring\ of biomolecules to man-made surfaces through the use of delocalised \molecular wires\ or carbon nanotubes are detailed as are the application of surface chemical and genetic engineering methods to the construction of robust, orientated biomolecular monolayers.